2022
DOI: 10.1002/cctc.202101875
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Friedel‐Crafts‐Alkylation‐Enantioselective‐Protonation by Artificial Enzyme Iminium Catalysis

Abstract: The incorporation of organocatalysts into protein scaffolds holds the promise of overcoming some of the limitations of this powerful catalytic approach. Previously, we showed that incorporation of the non-canonical amino acid para-aminophenylalanine into the non-enzymatic protein scaffold LmrR forms a proficient and enantioselective artificial enzyme (LmrR_ pAF) for the Friedel-Crafts alkylation of indoles with enals. The unnatural aniline side-chain is directly involved in catalysis, operating via a well-know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Roelfes and his group used the term "blank canvas" for the LmrR scaffold and proposed that the amino acid side chains in the LmrR scaffold's pocket could be exploited to promote a variety of catalytic processes. 48 Using ArMs, excellent enantioselectivity up to 99% (LmRr_A92E) was obtained. ArMs are a blossoming concept, and we firmly believe that their industrial potential will be shown up in the near future.…”
Section: ■ Summary and Outlookmentioning
confidence: 97%
See 1 more Smart Citation
“…Roelfes and his group used the term "blank canvas" for the LmrR scaffold and proposed that the amino acid side chains in the LmrR scaffold's pocket could be exploited to promote a variety of catalytic processes. 48 Using ArMs, excellent enantioselectivity up to 99% (LmRr_A92E) was obtained. ArMs are a blossoming concept, and we firmly believe that their industrial potential will be shown up in the near future.…”
Section: ■ Summary and Outlookmentioning
confidence: 97%
“…47 In one of their recent articles, the same group showed the potential of the LmrR_pAF scaffold for performing the challenging tandem F−C alkylation−enantioselective protonation (FC-EP) reaction. 48 Another noncanonical amino acid (8-hydroxyquinolin-3yl)alanine (HQAla) was also explored for catalyzing F−C reactions. Hydroxyquinoline has been used as an analytical reagent to bind transition metals through an N−O bidentate binding mode.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[116,[118][119][120] B. Organocatalytic artificial enzyme catalysed Friedel-Crafts alkylation [125] and (C.) tandem-enantioselective protonation reactions. [126] See references for full reaction conditions. features a designed catalytic triad based esterase active site.…”
Section: Artificial Enzymes and Dna Catalystsmentioning
confidence: 99%
“… A. Friedel‐Crafts alkylation catalysed by artificial enzymes based on copper(II) and MDR protein scaffolds [116,118–120] . B. Organocatalytic artificial enzyme catalysed Friedel‐Crafts alkylation [125] and (C.) tandem‐enantioselective protonation reactions [126] . See references for full reaction conditions.…”
Section: Artificial Enzymes and Dna Catalystsmentioning
confidence: 99%
See 1 more Smart Citation